THE RELATIONSHIP OF METACOGNTIVE KNOWLEDGE WITH METACOGNITIVE AWARENESS IN STUDENTS - Parestu, Bina Putri; Milama, Burhanudin; Fairusi, Dila (JCER (Journal of Chemistry Education Research), 2024)
The 2013 curriculum requires students to demonstrate metacognitive proficiency. The alignment of knowledge and metacognitive awareness can assist students in achieving the learning  objectives in the national curriculum. This study aimed to ascertain whether there was a correlation between metacognitive knowledge and metacognitive awareness among students. This study employed a correlational design research methodology. The instruments used to gather data including a set of 5 questions involved in testing students’ metacognitive knowledge. Meanwhile, The Metacognition Awareness Inventory (MAI) which comprised of 52 items was employed to assess metacognitive awareness.  The correlation between metacognitive knowledge and awareness can be measured using the Product Moment correlation coefficient. The findings of this study indicated that there was a positive  correlation between metacognitive knowledge and awareness yet it was relatively low (0.110).